2020
DOI: 10.3390/jcm9051263
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Systemic Inflammation Rather than Arterial Circulatory Dysfunction Predict Decompensation of Liver Cirrhosis

Abstract: Background: While systemic inflammation is recognized as playing a central role in the pathogenesis of organ failures in patients with liver cirrhosis, less is known about its relevance in the development of classical hepatic decompensation. Aim: To characterize the relationship between systemic inflammation, hemodynamics, and anemia with decompensation of liver cirrhosis. Methods: This is a post-hoc analysis of a cohort study of outpatients with advanced liver fibrosis or cirrhosis. Results: Analysis included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…HPVG is a marker of portal hypertension, but the invasive procedure is rarely justified in patients with compensated cirrhosis due to the risk of procedural complications. Other studies identified anaemia, markers of systemic inflammation like IL‐6 13 or vitamin D 14 levels as predictors of decompensation. No data on IL‐6 or vitamin D were available in the Explorys cohort but anaemia is indirectly represented by erythrocyte count, haematocrit and haemoglobin concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPVG is a marker of portal hypertension, but the invasive procedure is rarely justified in patients with compensated cirrhosis due to the risk of procedural complications. Other studies identified anaemia, markers of systemic inflammation like IL‐6 13 or vitamin D 14 levels as predictors of decompensation. No data on IL‐6 or vitamin D were available in the Explorys cohort but anaemia is indirectly represented by erythrocyte count, haematocrit and haemoglobin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with compensated cirrhosis, it is difficult to justify invasive HVPG measurement 12 . Other studies identified anaemia, markers of systemic inflammation like IL‐6 13 or vitamin D 14 levels as predictors of decompensation.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Bothou et al found that a low level of haemoglobin was a strongly Open access and independent predictor of hospital admission in outpatients with decompensated liver cirrhosis. 33 The mean value of haemoglobin reported by Bothou et al was 134 g/L. Anaemia can predict the development of ACLF in outpatients with cirrhosis, the median value was 108 g/L.…”
Section: Discussionmentioning
confidence: 89%
“…LC-A can occur in both compensatory LC (C-LC) and decompensated LC (D-LC). Due to obvious portal hypertension in patients with D-LC, haemodynamic disorders are very likely to occur, causing hepatic tissue ischaemia and hypoxia, and immunodeficiency renders D-LC patients vulnerable to secondary infections, leading to sepsis and further liver injury; thus, D-LC is rarely in a quiescent state[ 55 ]. Therefore, LC-A occurs in patients with C-LC more commonly than in those with D-LC.…”
Section: Non-aclf Aocldmentioning
confidence: 99%